Autonomic and psychological adaptations in Olympic rowers - Iellamo, F.; Pigozzi, F.; Spataro, A.; Di Salvo, V.; Fagnani, F.; Roselli, A.; Rizzo, M.; Malacarne, M.; Pagani, M.; Lucini, D. (The Journal of Sports Medicine and Physical Fitness, 2006)
Aim: Power spectral analysis of heart rate variability has been used to assess the time course of neurovegetative adaptations to training. This study was undertaken: 1) to evaluate whether and which indicator(s) of autonomic cardiac regulation and psychophysical stress can identify successful athletes during a training season culminating with the Olympic Games and 2) to evaluate the feasibility of a quasi-on-line assessment of autonomic cardiac regulation from training field, by a telematic approach. Methods: This study was conducted on the group of male athletes composing the Italian national team of rowing (n=34), in the season preceding the 2004 Olympic Games. Complete results are from 18 subjects (age 25.3±0.5 years), who were selected to participate to the Athens' Olympic games. Athletes were studied while partially detrained, at mid-training season and close to the games. The RR interval was obtained through a miniature transtelephonic-ECG recorder in the supine and standing posture, thus allowing the evaluation of cardiovascular responses to a sympathetic challenge. Data were downloaded through a telephone line, to the referral center where RR-interval variability data were analyzed with the autoregressive method. Also, in each study sessions, athletes filled a self-administered questionnaire of stress perception and somatic symptoms (4S-Q). Results: All ECG recordings were transmitted successfully by phone to the referral center. No significant difference was detected in any marker of autonomic cardiac regulation between athletes who won a medal at the Olympic Games and those who did not. However, respiratory rate was faster in medal winners (P=0.02), while the questionnaire addressing stress (4S-Q) provided greater scores in the group that did not win a medal (F=5.55, P<0.022) at mid-training season and close to the Olympic Games. Conclusions: The results of this study would suggest the possibility of an early detection of psychosomatic symptoms resulting from long duration and elevated stress of preparing for top level competitions, whose better handling might identify the most successful athletes. In addition, it indicates the feasibility of a quasi-on-line assessment of autonomic cardiac adaptations to strenuous training directly from field to be possibly used for improving individual training programs, allowing athletes evaluation in their natural environment.